O DOI-CODI carioca: memória e cotidiano no 'Castelo do Terror' - Bettamio, Rafaella Lúcia de Azevedo Ferreira (2012)
The objective of this thesis is to analyze the memory of six former political prisoners of the Destacamento de Operações de Informações-Centro de Operações de Defesa Interna do Rio de Janeiro, or DOI-CODI/RJ (Detachment of Information Operations Center-Internal Defense Operations Center of Rio de Janeiro), recently interviewed between 2002 and 2004, about their everyday living in that institution, in 1970. At that year, in the Sistema de Segurança Interna, or SISSEGIN (Internal Security System), the DOI-CODI had been created and distributed by all the country’s military regions, becoming the repression leading instituion of political opponents who oppted for armed struggle as a way to defeat Brazil’s military dictatorship. Thus, these six former prisioners narratives are, not only essencial sources, but the main study object of this paper. Through them, it becomes possible to access crucial aspects for the characterization of the daily lived by prisioners in one of these agencies - the DOI-CODI in Rio de Janeiro -, since this past connects to present through their memories. Therefore, in order to understand such memories, the training and the performance of the DOI-CODI are also analyzed here, placing the narratives of the interviewed former political prisioners in dialogue with a specially selected bibliography, and a source about DOI made by one of its agents, when that agency was still active, in 1978. In order to be applied to these memories an effective critique, necessary to all historical work, the study still focuses on the interferences that the present exerts on the construction that make in relation to the past lived in DOI-CODI/RJ, in order to clarify the basis on which are built at about thirty years later.